Revolutionizing Marketing: Unveiling the Quantum Theory of Consumer Engagement (Journal of Business, Universidad del Pacífico (Lima, Peru), 2023)
Marketing is a discipline that takes place in the transformation of an idea or visualization of how a business takes place in the market, being almost the perfect analysis of every little detail that can lead you to find those troubles that can be damaging to the business; must help potentialize the product or service marketing is probably the most competitive relationship in the market. This is because of the evaluation of competitors that we have to develop to perform a robust marketing plan and how this can be projected as if it was a fundamental part of the market, saying that far away from trying to convince a client to buy a product, is how emotionally and neurologically examined are being society, to be manipulated into believing these ideas that have been sold to them by the media, government, influencers and even economic status. The article aims to understand how companies manipulate customers into buying not just a product but also the client experience. It compiles global companies' experiences, starting from customer comments to data analysis and Neuromarketing strategies implemented by companies, governments, and states to formulate their plans and achieve their desired markets. Marketing is no longer just a tool, but a vital component in any market.